2015
DOI: 10.1017/s0021932015000243
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Children’s Height and Body Mass Index in Lithuania, 1990–2008

Abstract: The aim of the study was to reveal the ethnic and socioeconomic factors associated with height and body mass index (BMI) of children during the period of political and social transition in Lithuania in 1990-2008. Data were derived from the personal health records of 1491 children (762 boys and 729 girls) born in 1990 in Vilnius city and region. Height and BMI from birth up to the age of 18 years were investigated. Children were divided into groups according to their ethnicity, place of residence, father's and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Several studies conducted in developed and developing countries have shown a strong relationship between socioeconomic variables and the achieved height of children [38,39,40]. Children from poor households had worse linear growth outcomes than those from rich households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted in developed and developing countries have shown a strong relationship between socioeconomic variables and the achieved height of children [38,39,40]. Children from poor households had worse linear growth outcomes than those from rich households.…”
Section: Discussionmentioning
confidence: 99%
“…A related study found that boys had 77% higher odds of stunting [54]. The findings of different studies suggested that children from poor households tend to become lighter compared to the reference population, which can be attributed to the family's waning capacity to provide for and care for their children [36,38]. Excess energy loss and inadequate food intake could lead to undernourishment among growing school children.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of public health projects in China enhanced Chinese residents' health awareness and health knowledge and encouraged them to develop healthy habits [35,36].In addition, driven by the rapid economic development, the Chinese people's educational level has significantly improved as well. A number of studies showed that parents' social economic status, including education level, has a significantly positive influence on the height of children and adolescents [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, obese children tend to be taller before puberty compared to their normal weight peers ( 2 ) . In addition, family socioeconomic status (SES) generally shows a negative association with overweight and obesity in children ( 3 ) . So, it seems that an interactive effect exists between SES, height and childhood obesity, which we would like to explore more in the Irish part of the Childhood Obesity Surveillance Initiative (COSI).…”
mentioning
confidence: 99%